Just Your Average Muslim : The Unheard Voice - Zia Chaudhry (Grove Short Books, 2015)
This fascinating and original book provides a better insight into the life of "just your average Muslim" than you will find anywhere else. A powerful antidote to common but exhausted stereotypes, it challenges non-Muslims to reexamine their perceived ideas of what they think they know and Muslims to examine how they portray themselves to the world. It encourages us all to reflect on our similarities, not our differences.
Include Bibliography and Index.
Keywords: Muslims - Attitudes -- Muslims - Ethnic identity -- Great Britain